Laboratory and environmental decay of wood–plastic composite boards: flexural properties. Issue 2 (15th March 2018) - Ibach, Rebecca; Gnatowski, Marek; Sun, Grace; Glaeser, Jessie; Leung, Mathew; Haight, John
ABSTRACT: The flexural properties of wood–plastic composite (WPC) deck boards exposed to 9.5 years of environmental decay in Hilo, Hawaii, were compared to samples exposed to moisture and decay fungi for 12 weeks in the laboratory, to establish a correlation between sample flexural properties and calculated void volume. Specimens were tested for flexural strength and modulus, both wet and dry, at 23°C and 52°C. Some specimens degenerated to only 15% of original flexural strength. UV radiation had no impact on flexural properties of field-exposed boards; loss occurred mainly on the side opposite to the sun-exposed surface. The mechanism of the aging process on colonization of WPC by fungi was examined and is consistent with development of slow crack growth in the polyethylene matrix combined with wood decay by fungi. Wood particle decay, moisture, and elevated temperature were the major factors causing composite degradation, indicated by accumulation of voids and a severe decrease in flexural properties. To simulate long-term field impact (including decay) on WPC flexural properties in the laboratory, conditioning of specimens in hot water for an extended period of time is required. Exposure to water (70°C/5 days) was adequate for simulating long-term composite exposure in Hawaii of 4 × 15 × 86 mm 3 specimens.